Democracy, democratization and ideological conflicts/polarization in the contemporary muslim societies - Sahibuddin, Wahabuddin (2010)
Democratic peace theory assumes that Muslim societies would become better off if they democratize. The democratic experiences in Muslim societies such as Algeria (1991), Palestine (2006-2007), Iran (2009), Turkey, Egypt, etc. suggest that democratization of the Muslim societies has resulted in ideological polarization within Muslim societies and division of Muslims into supporters of secularism and proponents of political Islam. The Islamists-seculars relation radicalizes: (1) when the advocates of political Islam are prevented from participating in the political process and capturing power through democratic institutions and (2) when the advanced Western democratic states cooperate with nondemocratic secular elites of Muslim societies. The view that corruption, poverty, low literacy rate, tribalism, etc. may shed lights on possible reasons for failures of democracy in the Muslim world appears underestimating the reality. It does not explain the correlation between West’s economic aids to and political cooperation with selected governments of the Muslim world. It also does not explain the relationship between state or military’s intervention in, for instance, a relatively economically advanced Turkish society that enjoys high literacy rate. Academics have often neglected to investigate the relationship between philosophical dimension of democracy and philosophy of life prevalent in the Muslim world. Institutional and philosophical approaches to democracy and democratization are inseparable. It appears that democratization of Muslim societies in the image of Western liberal democracy is difficult. Yet, the institutional approach to democracy provides a common ground for cooperation between Islam and the West. The destabilizing role of democracy can be moderated if the debate between the Islamists, the seculars and the West focuses on issues that are human properties irrespective of religion, ethnicity or language.